2009
DOI: 10.1039/b918130j
|View full text |Cite
|
Sign up to set email alerts
|

New materials with detachable azobenzene: effective, colourless and extremely stable surface relief gratings

Abstract: New detachable azobenzene-containing materials produced via solid state reaction of urea formation were used for the inscription of effective, colourless and stable surface relief gratings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…A sophisticated solution has been reported that involves the formation of colorless SRGs by the use of the SRG-forming materials with detachable azobenzene units. 15,16 Another novel solution has also been reported that involves photoinduced SRG formation on films containing photochromic compounds other than azobenzenes in which one of the two stable isomers is colorless. [17][18][19][20] Finally, a solution of particular interest has been reported, in which SRGs on amorphous molecular films of photochromic spirooxazine were shown to be erasable by heating.…”
Section: Introductionmentioning
confidence: 99%
“…A sophisticated solution has been reported that involves the formation of colorless SRGs by the use of the SRG-forming materials with detachable azobenzene units. 15,16 Another novel solution has also been reported that involves photoinduced SRG formation on films containing photochromic compounds other than azobenzenes in which one of the two stable isomers is colorless. [17][18][19][20] Finally, a solution of particular interest has been reported, in which SRGs on amorphous molecular films of photochromic spirooxazine were shown to be erasable by heating.…”
Section: Introductionmentioning
confidence: 99%
“…Transparency SR films have been achieved using an azobenzene-containing polymeric film; the azobenzene groups were detached from the polymeric materials after SR formation, 13,14 but the fabrication process was complicated. Additionally, transparent photoreactive materials that are sensitive to the UV region have been investigated to form molecularly reoriented SR structures, but an annealing process is necessary for reorientation and SR formation.…”
mentioning
confidence: 99%
“…In addition, the position of the absorption bands of both the trans and cis state leads to typically yellow-colored coatings, which is often not desired. It has been shown that for specific linear azo polymers, this color can be removed, leading to permanent topographies [51]. Extensive research towards new applicable light triggered molecules [113] can lead to a more natural approach where the sun can be used as the light source [114].…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, Kim et al showed in 1995 that orthogonal recording of two gratings leads to a two-dimensional grating. Stumpe and co-workers have shown that these higher dimensional gratings can also be fabricated from more easily accessible azo-containing polymers [51,52], leading even to colorless gratings via decoupling of the azobenzene after recording [51]. They achieved this by decomposing the urea group connecting the azobenzene to the polymeric chain.…”
Section: Light-induced Permanent Surface Relief Gratings In Linear Azmentioning
confidence: 99%